2020
DOI: 10.1016/j.jclepro.2020.120895
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country evidence for social dimensions of urban water consumption during droughts

Abstract: A systematic literature review is carried out to understand the social dimensions driving the adoption of water saving behaviors in urban households. Salient aspects of the problem correspond to price elasticity of water demand, citizens' awareness of water value and water conservation intentions, the management of which is generally tackled through water price and non-price approaches. However, the evidence falls short to explain the social drivers and inhibitors of stable water consumption reductions. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 73 publications
(248 reference statements)
0
4
0
Order By: Relevance
“…People may access water from different sources; individual access to tap water at private households is different from collective efforts to appropriate water units from a CPR. Devising productive institutions and incentives to conserve the groundwater may differ from institutions in access to tap water (see (Asprilla Echeverría, 2020) and Chapter 2 -Social drivers of urban water consumption).…”
Section: Social Institutions In Groundwater Overexploitationmentioning
confidence: 99%
“…People may access water from different sources; individual access to tap water at private households is different from collective efforts to appropriate water units from a CPR. Devising productive institutions and incentives to conserve the groundwater may differ from institutions in access to tap water (see (Asprilla Echeverría, 2020) and Chapter 2 -Social drivers of urban water consumption).…”
Section: Social Institutions In Groundwater Overexploitationmentioning
confidence: 99%
“…Water conservation has long been a topic of interest with past research focused on stimulating household water conservation via different strategies (e.g., water pricing strategies, behavioural nudges, consumption feedback based on smart metering, educational programs, and communication messages; see e.g., Addo et al, 2018;Asprilla Echeverría, 2020). However, there is a general pitfall of many of these interventions as individuals are either not motivated after exposure to these interventions (Wallenborn, 2015) or the behavioural change slowly fades away (e.g., Asprilla Echeverría, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Contribution: I created a Water Security Index, which includes seven classes of indicators regarding water conservation information. (Echeverría, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, Echeverría (2020) analyzed 65 articles to understand the social dimensions driving the adoption of water-saving behaviors in urban households, focusing on the variations of water management strategies in different regions of the world. After presenting five key social categories of analysis reported in the literature -(i) water prices, (ii) water-saving devices, (iii) inflation of self-reported water savings, (iv) intention/behavior gaps and (v) weakening of water reductions -the author concluded that strategies to limit water consumption patterns are related to the availability of technological advances, time allocation preferences and the implementation of home appliances.…”
Section: Previous Systematic Reviewsmentioning
confidence: 99%